99mTc-imidodiphosphonate: a superior radio-pharmaceutical for in vivo positive myocardial infarct imaging. II: Clinical data. Issue 3 (March 1978) - Joseph, S P; Ell, P J; Ross, P; Donaldson, R; Elliott, A T; Brown, N J; Williams, E S
Abstract : 99mTc-Imidodiphosphonate was investigated as a new myocardial infarct imaging agent. In the acute phase, 50 patients admitted to the coronary care unit were serially scanned over a period of 7 days. A mobile gamma camera linked on line to a remote data processor was used. Because of higher uptake in infarcted myocardium and faster blood clearance, superior images than those recorded with 99mTc-pyrophosphate were obtained. Its ease of preparation, low cost, and favourable dosimetry (because of its label with conventional 99mTc) transforms this agent into the present radiopharmaceutical of choice for acute infarct imaging in particular if sizing and follow-up is intended versus time and type of treatment. In this series, no false positive cases were seen. The sensitivity of the method in the detection of full thickness myocardial infarction was 95%. It dropped to 70% in the detection of subendocardial infarction. However, some of these apparent false negative cases may reflect severe ischaemia without infarction. It is postulated that this discrimination may not always be realistic.